Clinical phenotypes of COPD - Vestbo, Jørgen (Henry Stewart Talks, 2012)
COPD, More than one disease, Definition of phenotypes, Consideration of subgroups of COPD, Traditional subgroupings, Recently defined subgroupings, What is the future of COPD?
Archived at 2021/02/25